2023
DOI: 10.1038/s41419-023-05608-3
|View full text |Cite
|
Sign up to set email alerts
|

CCN3/NOV promotes metastasis and tumor progression via GPNMB-induced EGFR activation in triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer. TNBC patients typically exhibit unfavorable outcomes due to its rapid growth and metastatic potential. Here, we found overexpression of CCN3 in TNBC patients. We identified that CCN3 knockdown diminished cancer stem cell formation, metastasis, and tumor growth in vitro and in vivo. Mechanistically, ablation of CCN3 reduced activity of the EGFR/MAPK pathway. Transcriptome profiling revealed that CCN3 induces glycoprotein nonme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…An example of this has been reported by Son et al (2023) demonstrating an oncogenic role for CCN3 in TNBC. Whether one can actually target CCN3 in advanced breast cancer has yet to be realized.…”
Section: Conclusion: a Birds’ Eye View Of The Ccn Field And Emerging ...mentioning
confidence: 76%
See 1 more Smart Citation
“…An example of this has been reported by Son et al (2023) demonstrating an oncogenic role for CCN3 in TNBC. Whether one can actually target CCN3 in advanced breast cancer has yet to be realized.…”
Section: Conclusion: a Birds’ Eye View Of The Ccn Field And Emerging ...mentioning
confidence: 76%
“…In another cancer, ovarian carcinoma, progression is also inhibited by downregulating CCN5 (Shi et al 2020). In terms of tumor vascularization studies from the Sabbah lab, Ferrand et al (2022) showed that enforced expression of CCN5 decreased network formation while knockdown of CCN5 increased vascular mimicry (VM).…”
Section: Ccn5 (Wisp-2)mentioning
confidence: 99%
“…However, it fulfills different roles in different cell types [ 23 , 24 ]. For example, in breast cancer cells, CCN3 increased cell proliferation by upregulating the expression of cyclin D1 [ 25 ]. Similarly, in pancreatic cancer cells, the overexpression of CCN3 facilitated cell proliferation and migration by inducing an epithelial–mesenchymal transition [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, CCN3 promotes the synthesis of bone morphogenetic proteins BMP, Runx2 and osterix in osteoblasts through GSK3β and β‐catenin signaling cascades (Chen et al 2021). CCN3 expression is upregulated in triple‐negative breast cancer patients, and it was found that CCN3 activates the EGFR pathway by inducing glycoprotein nonmetastatic melanoma protein B (GPNMB) expression (Son et al 2023). In primary rat chondrocytes, CCN3 exerts chondroprotective effects by inhibiting the PI3K/AKT/mTOR pathway (Huang et al 2019).…”
Section: The Expression Regulation Mechanism Of Ccn3mentioning
confidence: 99%